Host Genotype and Edaphic Factors Cumulatively Influence the Occurrence of Siderophore-producing Bacteria Associated with Rice (Oryza sativa L.) - Thuy, Phan; Wei-Ching, Chung; Li-Sen, Young (Vietnam Journal of Agricultural Sciences, 2022)
Seed-borne rice endophytes are capable of disseminating into host plant tissues as well as to their rhizosphere. Here, we investigated the occurrence of siderophore-producing bacteria (SPB) in the seed endospheres of two distinct rice (Oryza sativa L.) cultivars, TK8 (ssp. japonica) and TCN1 (ssp. indica), and their dissemination into the rhizospheres through culture-dependent methods. Their patterns of occurrence in the rhizospheres as well as in the root and shoot tissues of 30 day-old cultivars grown in three different kinds of soils were tested. The significance of SPB on Fe sequestration of TCN1 was studied using Enterobacter sp. LS-756. TK8 seeds were found to be not only abundant in endopsheric SPB (> 10-fold), but also exhibited enhanced SPB dissemination into the rhizosphere (1.3-fold) as compared to TCN1. The proportion of endophytic SPB was consistently higher in roots than in shoots, and it was found to decline with decreasing soil pH. A similar declining trend was further evident through the analysis of SPB composition in the rhizospheric and bulk soils. LS-756-inoculated TCN1 seedlings under low availability of Fe showed 32%, 178%, and 368% increases in Fe, chlorophyll, and chlorophyll b contents as compared to the uninoculated controls. Thus, the occurrence of seed-borne endophytic SPB and their dissemination into the rhizosphere vary significantly according to the rice genotype. Higher co-occurrence of SPB in the rhizosphere and internal root tissues of rice plants grown under Fe-limited conditions and the enhanced Fe uptake due to SPB inoculation substantiated their potential involvement in Fe sequestration.